Avenir Museum of Design and Merchandising building exterior - Unidentified photographer (Colorado State University. Libraries, 2016)
Photograph of the exterior of the Avenir Museum of Design and Merchandising building on opening day January 30, 2016.
Keywords: Fashion -- History; Fashion -- Exhibitions